GAME DEVELOPMENT IMPLEMENTATION OF TRADITIONAL VALUES OF CHARACTER IN THE 21ST CENTURY (International Conference on Elementary Education, 2018)
The traditional game is the type of game that is interesting to study. Along with access to the use of media technologies is growing very rapidly, and the 21st century is in sight, then the game is a traditional question, "Is it still necessary?". The use of media technologies bring changes tochild's play activity today. Traditional games as an a typical game to a region or country is now being abandoned. Modern games such as playstation, online games and gadgets is the type of game the most fun and liked children. Imagine, the gadget becomes child play facilities very quickly provide information according the wishes of children. Psychologically children who often play gadget will affect the development of his attitude. Kids are more likely to individualistic and difficult to interact with others. In contrast to traditional games which case it contains the noble values. FAnother interesting development related enomena manner in which humans are faced with in the 21st century with all its characteristics. Characteristic study skills a must-have in the 21st century is Creative, Communication, Collaboration and Critical Thinking. Along with the 21st century as the digital era, where the type of the modern game in the end it gives a negative impact. One of them is the problem of social skills that should have this skill possessed by children entering the 21st century, The purpose of this study was to find out how the implementation of the traditional games against the development of 21st century character values used method is to use the study. Researchers with the literature obtained in the end found that the implementation of the traditional game with all the values of the sublime in it affect the development of the character values in the 21st century.